Continuously Tunable 0.55-1.9-GHz Bandpass Filter With a Constant Bandwidth Using Switchable Varactor-Tuned Resonators - Feng Lin; Rais-Zadeh, Mina (IEEE transactions on microwave theory and techniques, 2017)
This paper reports on tunable 2- and 3-pole bandpass filters with a wide frequency tuning range (tuning ratio >3) and a constant bandwidth using switchable varactor-tuned resonators. The wide center frequency tuning range is obtained using p-i-n diodes to switch in and out quarter-wavelength (λ/4) or half-wavelength (λ/2) resonators for low-band or high-band modes, without increasing the tuning capacitance range of the varactors. A combination of electric and magnetic coupling is utilized to realize a near constant absolute bandwidth across the tuning range. A switchable feed line with a fixed matching capacitance is used to realize the external coupling. Two filters are designed and fabricated on a Duroid substrate with ε r = 2.2 and h = 0.787 mm. For the 2-pole filter, the center frequency is tuned from 550 to 1900 MHz while maintaining a 3-dB bandwidth of 92 ± 6 MHz, insertion loss of 3.2~4.4 dB, and return loss of better than 15 dB. For the 3-pole filter, the center frequency is tuned from 540 to 1800 MHz while maintaining a 3-dB bandwidth of 89 ± 4 MHz, insertion loss of 4~5.4 dB, and return loss of better than 12 dB. For both filter types, the third-order intercept point and 1-dB compression point (P 1 dB) are 11 and 7 dBm, respectively. The rejection level at 200-MHz offset frequency from the passband center frequency is better than 25 and 41 dB for 2- and 3-pole filters, respectively, across the entire tuning range. To the best of our knowledge, this planar bandpass filter exhibits the widest tuning range with a near-constant bandwidth.